PENGEMBANGAN GEL EKSTRAK ETANOL CABAI RAWIT (Capsicum frutescence L) - A. Hasrawati; Aztriana Aztriana (Fakultas Farmasi UMI, 2016)
Chili Pepper (Capsicum frutescence L) is a plant that can be used for the treatment of rheumatoid arthritis (RA). Chemical constituents contained in chili pepper is capsaicin, it was stimulate the nerves that can relieve pain. The purpose of this study was to determine the gel formulation of the ethanol extract of cayenne pepper which has optimal stability by using a variation of the base. In this study, the ethanol extract of cayenne pepper (2.5%) was made using synthetic gel base (carbopol) and semisynthetic gel base (sodium carboxymethylcellulose). Evaluation of the physical stability was tested using stress conditions method. The stability parameters were determined by organoleptic, viscosity and flow type. The ethanol extract of chili pepper was successfully created gel form by using 5% of sodium carboxymethylcellulose and 1% of carbopol as a gelling agent. There was no significant change of two formulas in stability evaluation before and after of the storage condition.